EXAMINING PRE-RETIREMENT ANXIETY AMONG LOCAL GOVERNMENT EMPLOYEES IN CROSS RIVER STATE, NIGERIA: A SURVEY-BASED STUDY (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
Retirement represents a significant life transition, often accompanied by anxiety stemming from uncertainties about financial security, social identity, and lifestyle changes. This study examines pre-retirement anxiety among local government employees in Cross River State, Nigeria, employing a survey-based approach to explore its prevalence, contributing factors, and demographic correlates. A cross-sectional design was utilized, with data collected from 450 local government employees nearing retirement (within five years) using the Nigerian Pre-Retirement Anxiety Scale (NPRAS). Findings revealed a high prevalence of retirement anxiety (78.4%), with financial preparedness (82.6%) and social alienation (74.2%) being the most prominent dimensions. Demographic factors such as age, gender, educational level, and years of service significantly influenced anxiety levels, with older employees and those with lower educational attainment reporting higher anxiety. Proactive personality traits and participation in retirement planning programs were associated with reduced anxiety. The study underscores the need for targeted interventions, including comprehensive retirement education and financial planning initiatives, to mitigate pre-retirement anxiety. Recommendations include policy reforms to enhance pension schemes and psychosocial support systems for local government employees. This research contributes to understanding retirement-related psychological challenges in a Nigerian context, offering insights for stakeholders to foster a smoother transition for retirees.